Deciphering yield formation process in wheat under contrasting tillage conditions - Sagar, Vidya; Yadav, Rajbir; Jain, Neelu; Gaikwad, K. B.; Prabhu, K. V. (The Indian Journal of Genetics and Plant Breeding, 2016)
Non-availability of the genotypes bred under conservation agriculture practices and presence of large interaction for genotype x management, points to the fact that the gain can be further consolidated through cultivation of specifically adapted genotypes under conservation agriculture (CA) in India. Differentially adapted 42 genotypes were grown for two consecutive years under three tillage conditions. During favorable year (2011-12) for crop growth, conservation agriculture (CA) provided the opportunity for benefits of traits like seed width, seed length, embryo width, initial vigour indicated by normalized difference vegetation index (NDVI), shoot biomass and days to maturity to be accumulated into higher biomass at harvest and higher grain yield realization due to improved harvest index (HI). Simultaneously, under conventional tillage raised bed condition probably due to poor water retention, traits relevant for moisture stress condition like NDVI 1 representing initial vigour and more ground coverage in vegetative stage, peduncle length, last node length, biomass, HI showed positive correlation with yield. Changing association between traits under different management condition warrants for caution in the selection criterion Path analysis shows that selection for higher biomass with better HI and higher yield under CA can lay foundation for realization of better gain for yield in future.